Analysis Of The Relationship And Contribution Of Metacognition Skills To Students Numeracy Literacy Skills - Jilan Najwa Asshifa; Muhammad Arie Firmansyah; Prawidi Wisnu Subroto (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2026)
The purpose of this study is to analyze the relationship between and the contribution of metacognitive abilities to students’ numeracy literacy skills. The study population consists of all students at SMP Negeri 3 Panongan, and the sample comprises 40 seventh-grade students in Class VII-3. The instruments used a 5-point Likert scale Metacognitive Awareness Inventory (MAI) questionnaire to assess metacognitive abilities and a test instrument to assess students’ numeracy literacy skills. Data analysis was conducted using Pearson’s correlation test and simple linear regression. The results of the study found: (1) There is a positive relationship between metacognitive ability and students’ numeracy literacy skills. (2) Metacognitive ability contributes 63.4% to numeracy literacy skills